Chemical composition of leaf and seed essential oil of Coriandrum sativum L. from Bangladesh - Mohammad Nazrul Islam Bhuiyan; Jaripa Begum; Mahbuba Sultana (Bangladesh Pharmacological Society, 2009)
The essential oils from leaves and fruits of Coriandrum sativum L. were analyzed by gas chromatography mass spectroscopy (GC-MS). The leaf oil contained 44 compounds mostly of aromatic acids containing 2-decenoic acid (30.8%), E-11-tetradecenoic acid (13.4%), capric acid (12.7%), undecyl alcohol (6.4%), tridecanoic acid (5.5%) and undecanoic acid (7.1%) as major constituents. The seed oil contains 53 compounds where the major compounds are linalool (37.7%), geranyl acetate (17.6%) and γ-terpinene (14.4%). The compositions of both oils varied qualitatively and quantitatively.